MicroRNAs as New Bioactive Components in Medicinal Plants - Xie, Wenyan; Weng, Alexander; Melzig, Matthias F. (Planta Medica, 2016)
Herbal medicine has been used to treat diseases for centuries; however, the biological active components and the mechanistic understanding of actions of plant-derived drugs are permanently discussed. MicroRNAs are a class of small, non-coding RNAs that play crucial roles as regulators of gene expression. In recent years, an increasing number of reports showed that microRNAs not only execute biological functions within their original system, they can also be transmited from one species to another, inducing a posttranscriptional repression of protein synthesis in the recipient. This cross-kingdom regulation of microRNAs provides thrilling clues that small RNAs from medicinal plants might act as new bioactive components, interacting with the mammalian system.In this article, we provide an overview of the cross-kingdom communication of plant-derived microRNAs. We summarize the microRNAs identified in medicinal plants, their potential targets in mammals, and discuss several recent studies concerning the therapeutic applications of plant-based microRNAs. Health regulations of herbal microRNAs in mammals are a new concept. Continuing efforts in this area will broaden our understanding of biological actions of herbal remedies, and will open the way for the development of new approaches to prevent or treat human diseases.
Keywords: miRNAs; medicinal plants; cross-kingdom; oral delivery; therapeutic agent; bioactive component